HUBUNGAN PENEMPATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. SHENG JEOU INDONESIA CIKANDE-SERANG - Indah Ratnawati; Pramudi Harsono; Wahyu Widodo (Universitas Bina Bangsa, 2022)
This study aims to determine the effect of Work Placement and Work Environment on Employee Performance of PT. Sheng Jeou Indonesia site Cikande-Serang. The research method used is a quantitative approach or statistical data analysis. What is meant by quantitative approach is research that focuses on presenting data in the form of numbers or quantitatively scored (scoring) using statistics. The sample used is saturated sampling, so the total is 60 samples. The results of the t-test of Work Placement on Employee Performance obtained the value of t count> t table, namely (12,533>1,67) meaning that Work Placement has an effect on Employee Performance. While the t-test of the work environment on employee performance obtained the value of t count < t table (-1.868 <1.67) meaning that the work environment has no effect on employee performance. Simultaneous research results (f test) obtained the value of f arithmetic > f table (659.466 > 2.76) meaning that Ha is accepted so that work placement and work environment simultaneously have a significant effect on employee performance. The R-Square value is 0.959% or 95.9%, the remaining 4.1% is influenced by variables not examined in this study